Strategies for Flood Mitigation - Ajay Kumar; Uma Kumari (International Journal of Rural and Regional Development, 2023)
The world has always experienced change. Water-too much or too little is the most common cause of migration and a city's downfall. The notable and significant distinction right now is that we are seeing it in real-time for the first time in human history. We contributed to the dangers that were produced, and we contributed to the remedies that will influence the pace and scope of change and disruption. We haven't really learned much from recent history, one could argue. We haven't left the floodplains; instead, we've expanded inside of them, destroying any natural features that may have shielded us from natural disasters. We are located near earthquake faults, storm, and tsunami pathways. The ecological advantages of the coastal zone ecologies, which support all life, have not been respected. Opportunities to direct growth and development have been turned down. Instead, we create default land-use patterns that are frequently immoral and ineffective. All of these actions have a negative impact on the environment, the economy, and our families. We have dumped our rubbish into the very water reservoirs that supply our kids' drinking water. But this time, we are more knowledgeable and capable. We have improved at grasping the larger picture. We have advanced technological skills in mapping and data resource analysis, and in some circumstances, real-time satellite weather monitoring, enabling preparation for some (but not all) extreme weather occurrences. We are intrigued by the special ability of the creative spirit. The threat of flooding is no longer specific to any one area, nation, or region but has spread worldwide. Floods now happen more frequently than ever before, which affects any location's socioeconomic structure. The frequency and severity of floods have increased to the point where they can occasionally become catastrophic and out of control. In the absence of such technology, a variety of tools, techniques, and data that can play a crucial role in forecasting, controlling, and mitigating various natural threats, such as floods, earthquakes, etc., were either impossible to gather or were extremely difficult and time-consuming to do so. It's time to recognize, comprehend, and respect natural drainage systems, and entire ecosystems, with the least amount of human intervention, and to learn how to adapt to floods and other inevitable natural events. Resilience is the primary design strategy that can support all the planning processes that can establish a symbiotic relationship with various natural processes and phenomena because we also realize that all the different types of events, such as climate change, earthquakes, tidal waves, or even flooding, are natural events and their occurrences are part of the evolution of the current earth's landscape.
Keywords: Food plains; coastal floating; deforestation; ecosystem; water resource